Effectiveness of cognitive restructuring technique to reduce academic pracrastination of vocational high school students - Saputra, Wahyu Nanda Eka (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
Academic procrastination is a serious problem among student. Academic procrastination refers to delaying in doing assignments and preparing for examinations until the last period of examination time and submission date of assignments. To solve this problem we could use cognitive restructuring technique. The purposes of this research are to gain the description of academic procrastination decrease by implementing the cognitive restructuring technique. This research used a single subject research as the research design. The type of the single subject research which used in this research is multiple baselines. The result of this research shows that academic procrastination had significant decrease by implementation the cognitive restructuring technique. This research gives advice for two parts. First, it will be better if counselor implement the cognitive restructuring technique to decreasing academic procrastination. Second, it will be better if stakeholder of school gives support to counselor for implementation the cognitive restructuring technique to decrease academic procrastination.